Numerical simulation and calibration of a single seam WAAM process with a commercial and an open source software / Alexander Bauer … [et al.] - Baeur, Alexander; Schart, Ronny; Halsig, Ander; Awiszus, Birgit (Smart Manufacturing Research Institute (SMRI), 2021)
This paper is dealing with the comparison of the FEM result quality between a commercial tool and an open source software with regards to the numerical simulation of a single seam WAAM process. For this purpose, an experimental WAAM process was conducted by a welding robot on a 1.4404 (316L) base plate with a 1.4404 (316L) welding wire, connected with the associated measurement equipment. Furthermore, the equivalent setup was transferred in the FEM tools Simufact Welding and Elmer FEM, using the same parameters for both simulations. The calculations show, that both programs are able to generate high quality results with a good accordance to the temperature development within the experimental processes. In summary it can be said, that both programs offer advantages and the decision what tool has to be used depends on the requirements and the possibilities of the user.